The parameters affecting the differences between the solutions corresponding to two different definitions of the reference surface of deformed rubber-like shells of revolution - Yükseler, RF (PERGAMON-ELSEVIER SCIENCE LTD, 2003)
The parameters affecting the differences between the solutions to problems related with incompressible rubber-like shells of revolution, undergoing axisymmetric finite strains and rotations, corresponding to two different definitions of the reference surface of deformed rubber-like shells of revolution are obtained through an asymptotic analysis. (C) 2002 Elsevier Science Ltd. All rights reserved.
Keywords: DEFORMATION; Mechanics